POTENSI BATANG TANAMAN YODIUM (Jatropha multifida Linn) SEBAGAI SENYAWA ANTIBAKTERI Staphylococcus aureus ATCC 25923 SECARA IN VITRO - Rokhana Rokhana; Ainiyah Ainiyah (Cendekia Journal of Pharmacy, 2019)
The search for bioactive compounds sources it continue to do because of the emergence of pathogenic bacteria that are resistant to antibiotics. Iodine plants(Jatropha multifida Linn) has flavonoids, alkaloids, tannins, saponins and jatropins. The flavanoid content in iodine plants can inhibit bacterial growth. Staphylococcus aureus is a pathogenic bacterium that can cause infections characterized by tissue damage accompanied by purulent abscesses. The purpose of this study was to determine the antibacterial activity of methanol extract of iodine plant stem against Staphylococcus aureus in vitro. Types of laboratory experimental research. The sample used in the study was iodine plant (Jatropha multifida Linn) extrac concentration used 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%. Using the Kirby bauer diffusion method. The results showed that there was antibacterial activity on iodine stems which showed a clear zone around the cactam disk at concentrations of 40% (10mm) 60% (12 mm), 80% (14mm), 100% (17 mm).